Mengukur Dampak Role Stress, Work-Family Conflict dan Emotional Exhaustion terhadap Cyberloafing pada Karyawan - Aliyah Zahrah; Lista Meria (Yayasan Literasi Sains Indonesia, 2025)
The ease of accessing the internet has led to the emergence of cyberloafing in the workplace. Cyberloafing, if not managed properly, can impact employee productivity. The purpose of this study was to determine and analyze the influence of role stress, work-family conflict, and emotional exhaustion on cyberloafing in employees. The population of this study was office employees in Tangerang. The number of samples in this study was 207 participants. Sampling used a purposive sampling technique with the criteria of employees who were married and aged <40 years. Data analysis used SEM-PLS. The results of the study proved that role stress had an effect on emotional exhaustion, but did not affect cyberloafing. The work-family conflict affected emotional exhaustion and cyberloafing. Then emotional exhaustion became a mediator between the influence of role stress on cyberloafing and the impact of work-family conflict on cyberloafing. This research can be a reference for company leaders to make SOPs that regulate cyberloafing which includes the formula of cyberloafing, restrictions on cyberloafing and sanctions if they violate predetermined limits.